Tendência genética em pesos e ganhos em peso de bovinos da raça Guzerá - deOliveira, J. A.; Lobo, R. B.; deOliveira, H. N. (Empresa Brasileira de Pesquisa Agropecuária (EMBRAPA), 1995)
The main objective of this study was to estimate genetic and phenotypic trends in weights at birth (BW), 8 (W8) and 12 months (W12) of age; and also in the daily gains from birth to 8 months (G8) and from birth to 12 months (G12) for the ''Guzera'' cattle herd from the ''Fazenda de Ensino e Pesquisa do Campus de Ilha Solteira'', UNESP, at Selviria, MS, in the Central-West region of Brazil. The data were collected between 1979 and 1984 from 842 calves, sired by 22 sires. Genetic trends were estimated by three alternative procedures, two of them were based on the methodology of repeated use of sires and the other procedure on the differences in the average genetic values of sires in the different years. The phenotypic annual changes estimated were -0.232 kg, -8.278 kg, -0.033 kg, -8.498 kg e -0.023 kg, for BW, W8, G8, W12 and G12, respectively. The estimates of genetic trends, obtained by the three procedures were different, but showed that genetic changes for all analised traits were little.

Objetivou-se, neste estudo, estimar as tendências fenotípicas e genéticas observadas nos pesos ao nascer (PN), aos oito (P8) e aos 12 meses (P 12) de idade e nos ganhos diários de peso do nascimento aos oito (G8) e aos 12 (G12) meses, em uma amostra de 842 animais Guzerá nascidos na Fazenda de Ensino e Pesquisa do Campus de Ilha Solteira, UNESP, no período de 1979 a 1984. As mudanças genéticas foram estimadas por três procedimentos alternativos, dois deles baseados no método do uso repetido de touros em anos sucessivos, e o terceiro procedimento nas diferenças entre os valores genéticos médios anuais de touros. As mudanças fenotípicas anuais foram de -0,232 kg, -8,278 kg, -0,033 kg, -8,498 kg e -0,023 kg, respectivamente para PN, P8, G8, P12 e G12. As estimativas das tendências genéticas anuais obtidas pelos três procedimentos diferiram entre si, mas indicaram que as mudanças genéticas em todas as características estudadas foram de pequena magnitude.
Genetic trends in weights and weight gains of ''Guzera'' cattle
Keywords: Beef cattle; phenotypic trends; birth weight; weaning weight; yearling weight